2017
DOI: 10.5539/ibr.v10n8p114
|View full text |Cite
|
Sign up to set email alerts
|

Experience Value, Satisfaction and Loyalty of International Tourists in Shanghai: A PLS-SEM Analysis

Abstract: The purpose of this paper is to explore loyalty and satisfaction of international tourists visiting Shanghai with tourism services through five experience value dimensions: functional value, price value, emotional value, social value and novelty value. A questionnaire was used to gather data from 166 international tourists visiting Shanghai during September-October, 2016. The measures were taken and adapted from William &Soutar (2009), andPrebensen &Rosengren (2016). Data was analyzed using SPSS 24 and SmartPl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Satisfaction is the most intuitive assessment of travel services by passengers (Fornell et al, 1996;Yuan et al, 2021), and it plays a pivotal role in monitoring and reflecting perceived quality and passenger behavior intentions. If passengers are satisfied with the service of a certain traveling mode, their intentions to repeatedly choose and word of mouth recommendation will increase (Krizek and El-Geneidy, 2007;Mustelier Puig and Ming, 2017). As marketing research has shown, passenger satisfaction impacts passengers' loyalty and complaints (Allen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction is the most intuitive assessment of travel services by passengers (Fornell et al, 1996;Yuan et al, 2021), and it plays a pivotal role in monitoring and reflecting perceived quality and passenger behavior intentions. If passengers are satisfied with the service of a certain traveling mode, their intentions to repeatedly choose and word of mouth recommendation will increase (Krizek and El-Geneidy, 2007;Mustelier Puig and Ming, 2017). As marketing research has shown, passenger satisfaction impacts passengers' loyalty and complaints (Allen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%